Extraperitoneal robot-assisted laparoscopic retroperitoneal lymph node dissection for early-stage testicular nonseminomatous germ cell tumors: A case report and literature review. Issue 49 (December 2017) - Qin, Jie; Wang, Ping; Jing, Taile; Kong, Debo; Xia, Dan; Wang, Shuo
Abstract: Rationale: Typically robot-assisted laparoscopic retroperitoneal lymph node dissection (R-RPLND) has been performed via a transperitoneal approach. Herein we report the first case of a novel R-RPLND using an extraperitoneal approach. Patient concerns: A 38-year-old man presented with an enlarging right scrotal mass. Diagnoses: Scrotal ultrasonography demonstrated a 5.5-cm solid mass of the right testis. The patient underwent right radical inguinal orchiectomy. Pathologic examination demonstrated a mixed germ cell tumor, predominately embryonal carcinoma with yolk sac tumor. Interventions: Extraperitoneal R-PRLND was performed 3 weeks after the radical orchiectomy. Outcome: The final pathologic examination showed a count of 19 lymph nodes, all of them negative. Normal antegrade ejaculation returned within 4 weeks postoperatively. No retroperitoneal recurrence or elevation of tumor marker levels were seen via surveillance imaging. Lessons: Our study shows that extraperitoneal R-RPLND is a safe and feasible procedure using an extraperitoneal approach that provides minimal invasion and rapid recovery of patients.